PENGARUH IKLIM KOMUNIKASI ORGANISASI DAN BUDAYA KERJA TERHADAP KINERJA GURU SMK PERTIWI BALIKPAPAN - jurnalpps pps; Bambang Sumarwoto; Indra Prasetyo; Sri Hartati (Prodi Magister Manajemen Universitas Wijaya Putra, 2022)
This study aims to determine how much influence the organizational communication climate and work culture have on the teaching performance of the Balikpapan Pertiwi SMKS teachers. This study uses a quantitative research method with a survey design using a questionnaire as a data collection tool. Based on data analysis, the results of the study found that the Organizational Communication Climate and Work Culture had a very high influence on the performance of the Balikpapan Pertiwi Senior High School teachers, which indicated that the teacher already had a sense of responsibility and commitment in carrying out work. Simultaneously, the school climate and work motivation affect the teaching performance of the Balikpapan Pertiwi Senior High School teachers in the low category (27.1%). The conclusion of this study is that the teaching performance level of the Balikpapan Pertiwi Senior High School teachers is influenced by the school climate variable and work motivation by 27.1% simultaneously. Meanwhile, the other 72.9% are influenced by other variables.